Breastfeeding and bottle feeding and their relationship with caries in early childhood. Literature review - Carrera Robalino, Alex (2018)
Introduction: Early childhood caries (ECC) is a health problem of worldwide interest. The purpose of this literature review is showed how an inadequate feeding practices by breastfeeding and bottle feeding contribute to early childhood caries. Materials and methods: A systematic online review of the existing literature from 2012 to 2018 was performed in the Medline database, using key words such as Caries, Breastfeeding, Bottle feeding and Childhood. Results: 61 articles were obtained, of which, 25 were considered in this review because they are considered to be related to the objective of this review. The literature reviewed showed a direct relationship between the presence of CIT and the way of feeding, with no difference between the types considered. Conclusions: Prolonged breastfeeding more than two years of age of the infant as well as the use of bottles added with sugars and carbohydrates constitute a direct risk for the CIT.